Biology and Treatment of High-Risk CLL: Significance of Complex Karyotype - Chatzikonstantinou, Thomas; Demosthenous, Christos; Baliakas, Panagiotis (Frontiers in Oncology, 2021)
Several reports highlight the clinical significance of cytogenetic complexity, namely complex karyotype (CK) identified though the performance of chromosome banding analysis (CBA) in chronic lymphocytic leukemia. Indeed, apart from a number of studies underscoring the prognostic and predictive value of CK in the chemo(immune)therapy era, mounting evidence suggests that CK could serve as an independent prognosticator and predictor even in patients treated with novel agents. In the present review, we provide an overview of the current knowledge regarding the clinical impact of CK in CLL, touching upon open issues related to the incorporation of CK in the clinical setting.